Global Context of Crises, and Local Patterns of Rivalry and Cooperation - Kibaroğlu, Ayşegül (The Middle East Studies Center at the Ohio State University, 2016)
Cooperation was essential between the three riparian nations if they were to effectively coordinate their use of the Tigris and Euphrates rivers. The global political environment presented obstacles, however. During the course of the Cold War the riparian nations found themselves in different political camps. The governments of Syria and Iraq had allied themselves with the Soviet Union and Turkey had joined the NATO coalition. This further stressed diplomatic ties, which in turn further stressed cooperation between the riparian water authorities.
Keywords: Crises; The Euphrates- Tigris; Water Politics